Hegel, Harding, and Objectivity - James, Christine (Southwest Philosophy Review, 1998)
Jean Hyppolite describes Hegel’s project in the Phenomenology of Spirit as “the development and formulation of natural consciousness and its progression to science, that is to say, to philosophic knowledge, to knowledge of the absolute” (Hyppolite 1974, 4). This development or progression is the “work of consciousness engaged in experience,” as phenomenal knowledge necessarily leads to absolute knowledge. Thus from the very nature of consciousness one is led toward the absolute, which is both substance as well as subject. This paper will argue that Hegel’s account of the development of consciousness and its progression towards knowledge has certain commonalities with feminist philosophy of science. Frequently, feminist theorists cite Hegel specifically in reference to his discussion of the master/slave relationship, or his discussion of ethics, two sections of the Phenomenology of Spirit in which Hegel explicitly attempts to delineate a role or place for women. Many of these sections do have decidedly anti-feminist implications, as has been correctly pointed out by many scholars. Especially in the section on Antigone, where Hegel ascribes the private sphere of life in the home to woman and the public sphere of life in the polis to man, Hegel is clearly unconcerned with the subordination of women, prescribing means of resistance, or finding alternatives to promote the removal of women’s oppression.1 Although Hegel’s political and moral theory does not reflect a feminist perspective, in this paper I will argue that Hegel’s theory of knowledge, the progress towards absolute knowledge described above, has much in common with recent feminist epistemology and philosophy of science. A central implication of this conclusion is that feminist theorists would do well to regard Hegel not merely politically, as an example of another “dead white male” philosopher who participated in the oppression of women; but also epistemologically, as a possible ally in the creation of better theories of knowledge that will regard the experience of culturally situated subjects as important sources of knowledge.2 This conclusion will be argued in two ways. First, I will illustrate how Hegel reconceptualizes the relationship between subject and object, and subject and community, and the related notion of objectivity. This type of objectivity will be shown to be a variety of “dialectical objectivity,” following Allan Megill’s delineation of four senses of objectivity. This reading of Hegelian subject-object relations and objectivity will then be compared to Sandra Harding’s concept of “strong objectivity,” a very similar type of dialectical objectivity which stands as an excellent example of current feminist epistemology and standpoint theory. From this similarity, it will be shown that Hegelian and feminist epistemology have much more in common than previously thought.
James, Christine (1998).Hegel, Harding, and Objectivity. Southwest Philosophy Review. 1 electronic record (PDF).
Keywords: Cognitive Science, Philosophy, Philosophy of Science, Phenomenology, Hegel, Standpoint feminist theory, Feminist Philosophy of Science